Marine Aquaculture Impacts on Marine Biota in Oligotrophic Environments of the Mediterranean Sea – A Review - Tičina, Vjekoslav; Katavić, Ivan; Grubišić, Leon (Frontiers in Marine Science, 2020)
The potential impacts of marine aquaculture are reviewed, focussing both on small-scale local effects near the farm environment and a broad spatial scale of many kilometres that impacts a number of different ecosystem components. Local changes in productivity, biodiversity and behavioural changes of wild fauna affected by nearby farm habitats were examined. Global aquaculture trends of growth perspectives as related to seafood supply, impacts on wild stock and biodiversity depletion, genetic changes in wild fish populations due to the escapement of cultured fish, capture-based aquaculture and its potential impacts on marine habitats were discussed. Adopting integrated principles in planning aquaculture development and respecting the assimilative capacity of a potential farming zone may reduce negative consequences of the aquaculture industry on the marine ecosystem.